CULINARY EDUCATION AND ITS INFLUENCE ON TOURIST DECISION-MAKING: A STUDY OF ASSAM - Das, Trinayanee Devi; Biswas, Soumendra Nath (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper discusses the impact of culinary education on the tourist decision-making process by explaining how food-related learning experiences, such as culinary schools, cooking classes, and food tours, shape tourists' perceptions of their choices in destinations, activities, and experiences. The study encompasses developing trends in culinary tourism, as culinary education significantly aligns with tourism and culture, emphasizing experiential food travel that extends beyond food events and fosters cross-cultural exchange. The influence of culinary education has been an important element of the food tourism industry, which plays a crucial role by influencing tourist decisions in destination selection and supporting the promotion of a destination. However, the ability and prospects of culinary education have not been fully recognized as competitive advantages by most practitioners in the food tourism industry. Little is known about how culinary education can affect tourists’ decisions in selecting.